(3TQM Gdabg GdCcHQ dCHj MfjaIs - (3GdeZfjSGhj, CHh GdefJgi, TgGH GdOjf, CMeO Hf eMeO, J (B1000 (3g`s ((3TfHg (B( (3YKeGf HGRGQj (B)s)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj gOGfG Edi WQjb GdSfI CeG HYO ajbhd CHh GdefJgj Ef cJGH Gdabg GdCcHQ GdPj Ufag GdEeGe GdCYXe cJGH UMjM ebHhd bGd GdHROhj aj CUhd Gdabg GdYde fhYGf GdJhMjO hGdUaGJ CQOJ Cf CLeY cdeGJ ef GdcJGH hGdSfIs
(3BNQgG (B:s
(3jgOj ef jTGA EdN cCfg aeG YdjfG EdG GdHdGZ hGddg jgOj ef jTGA Edi UQGW eSJbje Gddge jG gGOj GdegJOjf GgOfG GdUQGW GdeSJbjes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 234s
(3eYLe GdeDdajf (B1 / 298s
(3cTa GdXfhf (B2 / 1287s
(3gOjI GdYGQajf (B1 / 162s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs